(untitled) (Revista Puertorriqueña de Psicologia, 2016)
This article compares work centrality and central life interest in a sample of 208 employees in Puerto Rico divided into two groups: young and old. Two scale were administered to the sample: Work Centrality Scale (Andújar Rojas & Martínez Lugo, 1997) and Central Life Interests Scale (Perez & Martinez Lugo, 1997). Results showed a significant statistical difference between the means of the groups in work centrality (t(206)=-2.39, p<.05), obtaining the older employees the highest mean (49.88 vs 46.29). In the area of central life interests no statistical differences were obtained between the groups under study.